Framing Complexity in Formative Mesoamerica - Feinman, Gary M.; DeLance, Lisa L. (Book collections on Project MUSE., 2022)
"An examination of variable social and economic processes, Framing Complexity in Formative Mesoamerica explores nascent social complexity during the Preclassic/Formative period in Mesoamerica and addresses broader social questions about egalitarian and transegalitarian Pre-hispanic Mesoamerican cultural groups. The chapters explore social aggregation, emergence of ethnic affiliations, and regional and macro-regional variability."--